The confident parent : a pediatrician's guide to caring for your little one -- without losing your joy, your mind, or yourself - Scott, Jane, 1968-; Land, Stephanie (TarcherPerigee, 2016)
"We've all heard the complaint from parents: They're more overwhelmed than ever before -- juggling demands on their time as well as conflicting advice from family, friends, frenemies and "experts" on how to achieve parental perfection--or risk jeopardizing their little one's future happiness. Pediatrician Jane Scott has seen this parental anxiety up close, and in The Confident Parent she shares advice on how to cut through the confusion, dial down the insecurities and unhelpful advice, and simply do what countless parents around the world have done throughout history: tune in to their own instincts and respond to their little one's needs without overthinking, overstimulating, and overparenting. Informed by a unique global perspective -- before training at Duke and setting up her current practice in Colorado, Dr. Scott lived in England and Ireland, as well as the Australian outback and the South African desert -- The Confident Parent shows readers how to be not just better caregivers but happier and more balanced human beings. The book covers the basics of baby and child-care from breastfeeding to managing temper tantrums, offering a fresh perspective that is refreshingly liberating. Takeaways include: It is not "natural" or necessary for mothers to be with their young children all day and night. Nurturing a marriage or partnership is as important to child rearing as nurturing the child. Children are strong and resilient--unless parents teach them not to be. Picky eating is learned, not innate. There is such a thing as being too careful. Sometimes the less you know about the so-called rules of parenting, the better you are at it. This upbeat and empowering guide shows parents how small changes can yield big results -- helping them and their kids feel more secure, more confident, and more connected"--